The water-soluble fraction of extracellular polymeric substances from a resource recovery demonstration plant: characterization and potential application as an adhesive - Chen, Le Min; Erol, Özlem; Choi, Young Hae; Pronk, Mario; van Loosdrecht, Mark; Lin, Yuemei (Frontiers in Microbiology, 2024)
Currently, there is a growing interest in transforming wastewater treatment plants (WWTPs) into resource recovery plants. Microorganisms in aerobic granular sludge produce extracellular polymeric substances (EPS), which are considered sustainable resources to be extracted and can be used in diverse applications. Exploring applications in other high-value materials, such as adhesives, will not only enhance the valorization potential of the EPS but also promote resource recovery. This study aimed to characterize a water-soluble fraction extracted from the EPS collected at the demonstration plant in the Netherlands based on its chemical composition (amino acids, sugar, and fatty acids) and propose a proof-of-concept for its use as an adhesive. This fraction comprises a mixture of biomolecules, such as proteins (26.6 ± 0.3%), sugars (21.8 ± 0.2%), and fatty acids (0.9%). The water-soluble fraction exhibited shear strength reaching 36–51 kPa across a pH range of 2–10 without additional chemical treatment, suggesting a potential application as an adhesive. The findings from this study provide insights into the concept of resource recovery and the valorization of excess sludge at WWTPs.